TAFSIR SURAT AL-KAFIRUN (ANALISIS ATAS KITAB JAMI’ AL-BAYAN KARYA AL-THABARI) - Ridho, Muhammad (IAIN Bukittinggi, 2009)
Koran is a source in Islamic law, a kind of ways to understand Koran is by an exclamation. One of Islamic exclamation books is Jami’ul Bayan written by Imam alThabari one of Islamic scholars in the previous time. In this article, the writer is going to discuss how the scholar expert in exclamation wrote the exclamation book. Moreover, the writer is going to discuss about the surah alKafirun in the Koran.